2022
DOI: 10.3390/ijms232415459
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Performance of Undoped and Al-Doped ZnO Nanoparticles in the Degradation of Rhodamine B under UV-Visible Light:The Role of Defects and Morphology

Abstract: Quasi-spherical undoped ZnO and Al-doped ZnO nanoparticles with different aluminum content, ranging from 0.5 to 5 at% of Al with respect to Zn, were synthesized. These nanoparticles were evaluated as photocatalysts in the photodegradation of the Rhodamine B (RhB) dye aqueous solution under UV-visible light irradiation. The undoped ZnO nanopowder annealed at 400 °C resulted in the highest degradation efficiency of ca. 81% after 4 h under green light irradiation (525 nm), in the presence of 5 mg of catalyst. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…Both stacked particles exhibited similar average stacked sizes. Previous reports suggest that spherical ZnO nanoparticles tend to agglomerate into larger particles when a heat treatment is applied [14,40,41] . Sayed et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both stacked particles exhibited similar average stacked sizes. Previous reports suggest that spherical ZnO nanoparticles tend to agglomerate into larger particles when a heat treatment is applied [14,40,41] . Sayed et al.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports suggest that spherical ZnO nanoparticles tend to agglomerate into larger particles when a heat treatment is applied. [14,40,41] Sayed et al reported a morphologic study related to nanostructures with antibacterial activity. These authors suggest platelets with diamond-type-shape showing the highest antibacterial activity, compared to the large platelets and spherical structures.…”
Section: Itemmentioning
confidence: 99%
“…The remaining half of the tetrahedral sites and all octahedral sites remain unoccupied. Undoped ZnO exhibits n-type conductivity, which is commonly attributed to inherent defects such as excess zinc at interstitial positions and oxygen deficiencies [15].…”
Section: Introductionmentioning
confidence: 99%
“…In this Special Issue, Piras et al reported the influence of the defects and morphology of undoped and Al-doped ZnO nanoparticles on the photocatalytic degradation efficiency of Rhodamine B under UV-Visible [20]. The undoped ZnO nanopowder, annealed at 400 • C, resulted in the highest degradation efficiency of ca.…”
mentioning
confidence: 99%
“…The undoped ZnO nanopowder, annealed at 400 • C, resulted in the highest degradation efficiency of ca. 81% after 4 h under green light irradiation (525 nm) in the presence of 5 mg of catalyst [20]. Photoluminescence showed that the insertion of a dopant increases the oxygen vacancies, reducing the peroxide-like species responsible for photocatalysis [20].…”
mentioning
confidence: 99%